2011
DOI: 10.1007/s00299-011-1195-7
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of ex vitro pineapple (Ananas comosus L. Merr. var MD-2) as CAM or C3 is regulated by the environmental conditions

Abstract: Many plant species grown under in vitro controlled conditions can be used as models for the study of physiological processes. Adult pineapple can display CAM physiology while in vitro it functions as a C3 plant. Ex vitro Ananas comosus has plastic morphology and physiology, both easy to modify from C3 to CAM by changing the environmental conditions. The yield of survival for a rentable propagation protocol of pineapple is closely related with the C3/CAM shift and the associated physiological characteristics. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…The growth regulator, flask closure system and sucrose concentration in the culture medium affect plantlet survival in acclimatization, since these factors may affect the metabolism, modifying the morphological and physiological characteristics of the plants (Lucchesini and Mensuali-Sodi, 2004;Sáez et al, 2012). In addition to the modifications of in vitro culture conditions, several acclimatization procedures can be used, especially those which prevent water loss and biochemical disorders (Aragón et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The growth regulator, flask closure system and sucrose concentration in the culture medium affect plantlet survival in acclimatization, since these factors may affect the metabolism, modifying the morphological and physiological characteristics of the plants (Lucchesini and Mensuali-Sodi, 2004;Sáez et al, 2012). In addition to the modifications of in vitro culture conditions, several acclimatization procedures can be used, especially those which prevent water loss and biochemical disorders (Aragón et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Plant length was significantly less after 15 and 30 d than it was at day 0, but by day 45 had regained the height at day 0. Aragon et al (2012) found that stress imposed by water deficit and higher photosynthetic photon flux switched pineapple plants from C3 to CAM behavior. In our results we can find more number of roots, higher fresh weight and photosynthetic activity at 45 d in acclimatization period to report for this author at 56 d in CAM induced pineapple.…”
Section: Resultsmentioning
confidence: 96%
“…Leaves pH determination: Six fresh D-leaves of plants were collected every 3 h for 24 h. Samples were crushed and 0.5 ml of the resulting fluid were collected, clarified by addition of activated charcoal and centrifuged at 12,000 g during 5 min. Supernatant pH was immediately quantified with pH indicator strips (Merck KGaA 64,271) according to Aragón et al (2012) [13].…”
Section: Chlorophyll Content Determinationmentioning
confidence: 99%
“…Temperature determines the occurrence of C 3 or CAM photosynthesis in pineapple plantlets grown under in vitro conditions [11], this behavior is also modulated by nitric oxide and water availability [12]. Besides C 3 or CAM metabolism in pineapple plantlets was conditioned by a combination of low relative humidity, and high temperatures and light intensity during the 4 first weeks of ex vitro growth [13] [14]. It is known that adult macro-propagated pineapple plants are classified like "strong constitutive CAM plants" [15]- [18].…”
Section: Introductionmentioning
confidence: 99%